Coping and Social Adjustment in Pediatric Oncology: From Diagnosis to 12 Months. (15th September 2020) - Desjardins, Leandra; Rodriguez, Erin; Dunn, Madeline; Bemis, Heather; Murphy, Lexa; Manring, Samantha; Winning, Adrien; Vannatta, Kathryn; Gerhardt, Cynthia A; Compas, Bruce E
Abstract: Objective: Children diagnosed with cancer experience stress associated with their diagnosis and treatment and are at heightened risk for problems in social adjustment. This study investigated the association between coping with cancer-related stress and problems in social adjustment across the first year after a pediatric cancer diagnosis. Methods: Mothers of children (ages 5–17 years) with cancer ( N  =   312) were recruited from two children's hospitals. Mother's reported on their child's social adjustment and coping near diagnosis (T1) and 12 months (T2). Results: Primary, secondary control, and disengagement coping were significantly associated with concurrent social adjustment at 12 months. The bivariate associations between baseline primary and secondary control coping and social problems 12 months later were no longer significant in a multivariate regression model. Conclusions: These findings inform our understanding of the association between coping with cancer-related stress and social adjustment of children diagnosed with cancer. Interventions teaching primary and secondary control coping strategies for cancer-related stressors may offer some benefit to concurrent youth social adjustment. Further research is needed on how best to support social adjustment in this population over time.